PLGA (poly (lactic-co-glycolic acid)) with linear degradation behavior in vitro as well as preparation method and application of PLGA

By using the synergistic effect of chiral 3-methylglycolate and chiral ligand in PLGA synthesis, a complete alternating PLGA synthesis with high stereoselectivity and low side reactions is achieved, and the lack of regio-selectivity in the prior art is solved. and the problem of many side reactions, materials with high melting point and linear degradation characteristics have been obtained, which are suitable for controlled drug delivery.

CN119119431APending Publication Date: 2024-12-13QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411276472.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

There are problems of insufficient regional selectivity and many side reactions in existing PLGA synthesis, which leads to alternating structural defects, affecting the controllability and thermal performance of its degradation behavior.

Method used

Use chiral 3-methylglycolic acid ester and chiral ligand to add trimethylaluminum or aluminum isopropanol solution to toluene, add polymer monomer and alcohol compound initiator to control the reaction temperature and time to achieve high Complete alternating PLGA synthesis of stereoselective and low side reactions.

Benefits of technology

Complete alternating PLGA with high stereoselectivity greater than 99%, high melting point and good thermal stability were obtained. It is suitable for controlled drug delivery materials, with linear degradation characteristics and high economic value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119431A_ABST
    Figure CN119119431A_ABST
Patent Text Reader

Abstract

The invention discloses PLGA (poly (lactic-co-glycolic acid)) with linear degradation in vitro degradation behavior as well as a preparation method and application thereof, and belongs to the technical field of polymer medical materials and preparation thereof. According to the invention, 3-methyl glycolate is used as a raw material, and the completely alternating PLGA with regioselectivity greater than 99% is prepared through ring-opening polymerization of 3-methyl glycolate only at glycolic acid sites. The completely alternating PLGA prepared by the invention is a new material synthesized for the first time, has the characteristics of higher melting point, better thermal stability, higher crystallinity and linear degradation compared with a non-completely alternating PLGA material, is expected to be used as a novel controllable drug delivery material, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to PLGA with linear degradation behavior in vitro and a preparation method and application thereof, belonging to the technical field of polymer medical materials and preparation thereof. Background Art

[0002] Biodegradable polyesters have been developed rapidly in recent years as an important alternative to traditional fossil-based plastics. A series of new biodegradable polyesters such as PLA, PGA, PHA, etc. have been developed and widely used in packaging, agriculture, pharmaceuticals and other fields. Among these materials, alternating poly(lactic-co-glycolic acid) (PLGA) has received special attention due to its unique microstructure. It is composed of an L unit (lactic acid) and a G unit (glycolic acid) in an alternating order. Completely alternating PLGA has only one linking unit, LG, while non-completely alternating PLGA has three linking units, LL, LG, and GG. Compared with non-alternating PLGA, alternating PLGA has more controllable degradation behavior and is therefore considered to be an ideal material for controlled drug delivery. This is because the degradation behavior of PLGA is highly related to its chain structure, in which the degradation rates of the three linking units are from fast to slow: GG>LG>LL. When using non-completely alternating PLGA as a drug carrier, the drug release is uncontrolled due to the nonlinear degradation of the carrier, which may lead to sudden changes in local pH and fluctuations in drug release. Therefore, to achieve controlled release of drugs, it is necessary to avoid generating GG or LL linking units in PLGA carriers as much as possible. That is, exploring the synthesis method of completely alternating PLGA has important research and application value.

[0003] Currently, commercial PLGA is mostly prepared by the polycondensation reaction of glycolic acid and lactic acid, and the resulting PLGA does not have an alternating structure. In the synthesis of alternating PLGA, the regioselective ring-opening polymerization of chiral 3-methyl glycolate (MeG) is an effective method for synthesizing alternating PLGA. However, there are still two difficulties in achieving the synthesis of completely alternating PLGA through this route: (1) Complete regioselectivity has not yet been achieved in the ring-opening polymerization of MeG; (2) There is a transesterification side reaction in the reaction. These problems have hindered the synthesis of completely alternating PLGA. In recent years, researchers have conducted a lot of research on this route and have achieved the synthesis of PLGA with a certain degree of alternation. For example, Qiu's group demonstrated that when using octanoic acid as a catalyst, the ring-opening polymerization of MeG monomer can only achieve moderate regioselectivity (85%). The ring opening of MeG monomer essentially tends to favor the G site with less steric hindrance. In 2020, Satoh's group reported the ring-opening polymerization of (S)-MeG using a phosphazene base as a catalyst. The catalyst tends to open the ring at the more electrophilic L site, with a regioselectivity of 95% at -78°C. It is worth noting that due to the regional defects in the polymer microstructure, both PLGAs have no melting point. In 2021, based on the synergistic effect of steric hindrance and chirality control, the Coates group used the chiral (SalBinam)AlOR complex to synthesize an alternating PLGA with a regioselectivity of up to 98%. However, even for PLGA with a high regioselectivity of 98%, its melting point is still unclear, indicating that the few structural defects in the polymer have a serious impact on the thermal properties of PLGA. The existing catalytic system can only achieve limited regioselectivity, and it is impossible to completely avoid the ester exchange side reaction in the polymerization reaction, resulting in the formation of GG or LL bonds in the PLGA chain. It is still inevitable. The presence of a small amount of GG or LL bonds in these polymer chains will further lead to fluctuations in the degradation rate of PLGA. Therefore, it is necessary to further improve the regioselectivity of 3-methylglycolate (MeG) in the ring-opening polymerization and inhibit the side reactions in the reaction to achieve the synthesis of completely alternating PLGA. Summary of the invention

[0004] The object of the present invention is to provide a PLGA whose in vitro degradation behavior is linear degradation, that is, a completely alternating PLGA.

[0005] The technical solution of the present invention:

[0006] One of the purposes of the present invention is to provide a PLGA with linear degradation behavior in vitro. The PLGA is a GL alternating structure, wherein G is a glycolic acid unit, L is a glycolic acid unit, and the number ratio of G units and L units in PLGA is the same.

[0007] It is further defined that the G units and L units in PLGA are arranged in a completely alternating order, the stereoselectivity is greater than 99%, and the MALDI-TOF mass spectrum has a single distribution of mass peaks with an interval of 130.

[0008] Further defined, the number average molecular weight of PLGA is 2000-100 kg / mol, the molecular weight distribution is 1.01-2.0, and the glass transition temperature T g The melting transition temperature is 30-60°C. m 90~160℃.

[0009] Further defined, the structural formula of PLGA is as follows:

[0010]

[0011] The second object of the present invention is to provide a method for preparing the above-mentioned PLGA, which specifically comprises: dissolving a chiral ligand in toluene, adding trimethylaluminum or aluminum isopropoxide solution dropwise, adding a polymerization monomer, adding an initiator, reacting at a reaction temperature for 10 minutes to 100 hours, quenching with cold methanol or n-hexane, and vacuum drying to obtain PLGA.

[0012] Further defined, the chiral ligand structural formula is as follows:

[0013]

[0014] It is further defined that the polymerization monomer is chiral 3-methyl glycolate.

[0015] Further defined, the polymerizable monomer structural formula is as follows:

[0016]

[0017] Further defined, the initiator is an alcohol compound with the structural formula ROH or a compound with the structural formula (RO) x The invention relates to a metal alkoxide of M, wherein R is a straight chain or branched alkyl group having 1 to 10 carbon atoms or a benzene ring having a substituent, wherein the substituent includes a group containing or not containing oxygen or nitrogen heteroatoms, X is 1 to 4, and M is a metal ion.

[0018] In a further embodiment, the initiator is benzhydrol.

[0019] It is further defined that the reaction temperature is -30 to 110°C.

[0020] It is further defined that the molar ratio of the chiral ligand to the polymerization monomer is 5:1 to 0.0001:1.

[0021] The third object of the present invention is to provide an application of the above PLGA, specifically as a drug controllable delivery material.

[0022] It is further defined that the drug controllable delivery material is formed by mixing a L-poly(lactic-co-glycolic acid) polymer and a D-poly(lactic-co-glycolic acid) polymer in a mass ratio of 1:1.

[0023] Further defined, the glass transition temperature T of the drug controllable delivery material g Between 30 and 60°C, the melting transition temperature T m Between 160 and 240°C.

[0024] Beneficial effects:

[0025] The present invention provides a method for synthesizing a completely alternating PLGA, wherein the polymerization reaction is only ring-opened at the glycolic acid site, the reaction activity is high, the reaction conditions are mild, the yield is high, the side reactions are few, the operation is simple, and the post-processing is convenient. The completely alternating PLGA obtained by the present invention has a higher melting point, better thermal stability, higher crystallinity, and linear degradation characteristics compared to PLGA on the market and reported in the literature, and is expected to be used as a new controllable drug delivery material with high economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The completely alternating PLGA prepared in Example 1 1 HNMR spectrum;

[0027] Figure 2 This is the GPC spectrum of the completely alternating PLGA prepared in Example 1;

[0028] Figure 3 This is the DSC spectrum of the completely alternating PLGA prepared in Example 1;

[0029] Figure 4 This is the WAXD spectrum of the completely alternating PLGA prepared in Example 1;

[0030] Figure 5 This is a comparison chart of the in vitro degradation curves of the completely alternating PLGA (red) prepared in Example 4 and the commercial PLGA (black). DETAILED DESCRIPTION

[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0033] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0034] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art, and the purity of the solid and liquid reagents used is analytically pure.

[0035] Example 1

[0036] The reaction process of preparing completely alternating PLGA in this embodiment is as follows:

[0037]

[0038] The specific operation process is as follows:

[0039] (R)-MeG (130.1 mg, 1 mmol, 100 eq.) was dissolved in dichloromethane (1.0 mL) and placed in a 5 mL reaction tube. (S)-L1 (0.02 mmol, 2 eq.) was dissolved in toluene (1 mL), and the temperature of the reaction system was controlled at room temperature, and then trimethylaluminum solution (20 μL, 0.02 mmol, 1 eq.) was added dropwise. Then it was added dropwise to the reaction tube. A toluene solution of the initiator benzhydrol (20 μL, 10 μmol, 1 equivalent) was added, stirred for 1 min, and then reacted at room temperature. The reaction was terminated after 50 h, and the reaction was quenched with cold methanol to obtain a molecular weight M n =16.3kDa, molecular weight distribution The alternation degree P=0.99, the stereoselectivity of PLGA>99%, and the reaction conversion rate are 94%.

[0040] Example 2

[0041] The reaction process of preparing completely alternating PLGA in this embodiment is as follows:

[0042]

[0043] The specific operation process is as follows:

[0044] (R)-MeG (130.1 mg, 1 mmol, 100 eq.) was dissolved in dichloromethane (1.0 mL) and placed in a 5 mL reaction tube. (S)-L1 (0.02 mmol, 2 eq.) was dissolved in toluene (1 mL), and the temperature of the reaction system was controlled at room temperature, and then trimethylaluminum solution (20 μL, 0.02 mmol, 1 eq.) was added dropwise. Then it was added dropwise to the reaction tube. A toluene solution of the initiator benzhydrol (20 μL, 10 μmol, 1 equivalent) was added, stirred for 1 min, and then reacted at 60 ° C. The reaction was terminated after 7 h, and the reaction was quenched with cold methanol to obtain a molecular weight M n =15.5kDa, molecular weight distribution The alternation degree P = 0.99, the stereoselectivity > 99% of PLGA, the reaction conversion rate is 98%, and the obtained PLGA 1 H NMR spectra, GPC spectra, DSC spectra and WAXD spectra, such as Figure 1-Figure 4 shown.

[0045] Example 3

[0046] The reaction process of preparing completely alternating PLGA in this embodiment is as follows:

[0047]

[0048] The specific operation process is as follows:

[0049] (R)-MeG (130.1 mg, 1 mmol, 100 eq.) was dissolved in dichloromethane (1.0 mL) and placed in a 5 mL reaction tube. (S)-L1 (0.02 mmol, 2 eq.) was dissolved in toluene (1 mL), and the temperature of the reaction system was controlled at room temperature, and then trimethylaluminum solution (20 μL, 0.02 mmol, 1 eq.) was added dropwise. Then it was added dropwise to the reaction tube. A toluene solution of the initiator benzhydrol (20 μL, 10 μmol, 1 equivalent) was added, stirred for 1 min, and then reacted at 0 ° C. The reaction was terminated after 90 h, and the reaction was quenched with cold methanol to obtain a molecular weight M n =16.0kDa, molecular weight distribution The alternation degree P=0.99, the stereoselectivity of PLGA>99%, and the reaction conversion rate are 98%.

[0050] Example 4

[0051] The reaction process of preparing completely alternating PLGA in this embodiment is as follows:

[0052]

[0053] The specific operation process is as follows:

[0054] (R)-MeG (260.2 mg, 2 mmol, 200 eq.) was dissolved in dichloromethane (1.0 mL) and placed in a 5 mL reaction tube. (S)-L1 (0.02 mmol, 2 eq.) was dissolved in toluene (1 mL), and the temperature of the reaction system was controlled at room temperature, and then trimethylaluminum solution (20 μL, 0.02 mmol, 1 eq.) was added dropwise. Then it was added dropwise to the reaction tube. A toluene solution of the initiator benzhydrol (20 μL, 10 μmol, 1 equivalent) was added, stirred for 1 min, and then reacted at 60 ° C. The reaction was completed after 11 h, and the reaction was quenched with cold methanol to obtain a molecular weight M n =29.7kDa, molecular weight distribution The alternation degree P=0.99, the stereoselectivity of PLGA>99%, and the reaction conversion rate are 90%.

[0055] The PLGA obtained in this example was subjected to an in vitro degradation experiment, and the specific degradation process was as follows:

[0056] PLGA was hot pressed into a film at 170°C. After weighing, the PLGA film was placed in a pre-weighed glass bottle. 30 mL of phosphate buffer (pH 7.4) was added to the bottle. Degradation experiments were performed at 37°C without stirring. The buffer solution was replaced every two days or after each sampling to prevent pH changes caused by polymer degradation. After a period of time, the buffer in the bottle was poured out and then rinsed with water three times. The sample was then dried for at least 24 hours until the weight no longer changed. The remaining mass was weighed and recorded.

[0057] The in vitro degradation performance of the PLGA was compared with that of the existing commercial PLGA. Figure 5 As shown by Figure 5 It can be seen that for the completely alternating PLGA film, within 15 days, the film quality was observed to decrease linearly, showing the characteristics of linear degradation. By calculation, it can be concluded that its degradation rate is 0.26997±1.63*10 -2 day -1 (like Figure 5 Middle red curve, R 2 =0.98). In contrast, the degradation rate of commercial PLGA is not linear, and the degradation rate increases gradually with the reaction time (e.g. Figure 5 Therefore, the completely alternating PLGA has the characteristics of controlled degradation.

[0058] Example 5

[0059] The reaction process of preparing completely alternating PLGA in this embodiment is as follows:

[0060]

[0061] The specific operation process is as follows:

[0062] (R)-MeG (130.1 mg, 1 mmol, 100 eq.) was dissolved in toluene (1.0 mL) and placed in a 5 mL reaction tube. (S)-L1 (0.02 mmol, 2 eq.) was dissolved in toluene (1 mL), and the temperature of the reaction system was controlled at room temperature, and then trimethylaluminum solution (20 μL, 0.02 mmol, 1 eq.) was added dropwise. It was then added dropwise to the reaction tube. A toluene solution of the initiator benzhydrol (20 μL, 10 μmol, 1 equivalent) was added, stirred for 1 minute, and then reacted at 80 ° C. The reaction was completed after 7 hours, and the reaction was quenched with cold methanol to obtain a molecular weight M n =16.9kDa, molecular weight distribution The alternation degree P=0.99, the stereoselectivity is>99% of PLGA, and the reaction conversion rate is>99%.

[0063] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A PLGA having a linear degradation behavior in vitro, characterized in that: The PLGA is a GL alternating structure, wherein G is a glycolic acid unit, L is a glycolic acid unit, and the number ratio of the G unit and the L unit in the PLGA is the same.

2. The PLGA according to claim 1, characterized in that The G units and L units in PLGA are arranged in a completely alternating order, the stereoselectivity is greater than 99%, and the MALDI-TOF mass spectrum has a single distribution of mass peaks with an interval of 130.

3. The PLGA according to claim 1, characterized in that The number average molecular weight of PLGA is 2000~100kg / mol, the molecular weight distribution is 1.01~2.0, and the glass transition temperature T g The melting transition temperature is 30-60°C. m 90~160℃.

4. A method for preparing PLGA according to any one of claims 1 to 3, characterized in that: The chiral ligand is dissolved in toluene, trimethylaluminum or aluminum isopropoxide solution is added dropwise, and then a polymerization monomer and an initiator are added. The reaction is carried out at the reaction temperature for 10 minutes to 100 hours, and the reaction is quenched with cold methanol or n-hexane and then vacuum dried to obtain PLGA.

5. The preparation method according to claim 4, characterized in that: The chiral ligand structure is as follows:

6. The preparation method according to claim 4, characterized in that: The polymerization monomer is chiral 3-methyl glycolate.

7. The preparation method according to claim 4, characterized in that: The initiator is an alcohol compound with the structural formula ROH or a compound with the structural formula (RO) x The invention relates to a metal alkoxide of M, wherein R is a straight chain or branched alkyl group having 1 to 10 carbon atoms or a benzene ring having a substituent, wherein the substituent includes a group containing or not containing oxygen or nitrogen heteroatoms, X is 1 to 4, and M is a metal ion.

8. The preparation method according to claim 4, characterized in that: The reaction temperature is -30 to 110°C.

9. The preparation method according to claim 4, characterized in that: The molar ratio of the chiral ligand to the polymerization monomer is 5:1 to 0.0001:

1.

10. A use of PLGA according to any one of claims 1 to 3, characterized in that: Used as a controlled drug delivery material.

Citation Information

Patent Citations

  • Alternating poly(lactic-co-glycolic acid) and methods of making and using same

    US20240150520A1